2012
DOI: 10.1016/j.bpj.2011.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Actin Filament Elasticity and Retrograde Flow Shape the Force-Velocity Relation of Motile Cells

Abstract: Cells migrate through a crowded environment during processes such as metastasis or wound healing, and must generate and withstand substantial forces. The cellular motility responses to environmental forces are represented by their force-velocity relation, which has been measured for fish keratocytes but remains unexplained. Even pN opposing forces slow down lamellipodium motion by three orders of magnitude. At larger opposing forces, the retrograde flow of the actin network accelerates until it compensates for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
105
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(124 citation statements)
references
References 78 publications
15
105
2
1
Order By: Relevance
“…By using the equation provided by Fuerstman et al (18) [channel dimensions 6 μm wide and 3 μm high, viscosity of water 1 mPa·s, channel length 100 μm, and cell (fluid) velocity of 0.3 μm/s], we found that the net force to move this column of water was on the order of 1 pN. Usami et al, observing confined neutrophils in micropipettes (22), and others in unconfined settings (23)(24)(25), have shown that forces on the order of tens of nanonewtons are required to stall cell motion.…”
Section: Discussionmentioning
confidence: 99%
“…By using the equation provided by Fuerstman et al (18) [channel dimensions 6 μm wide and 3 μm high, viscosity of water 1 mPa·s, channel length 100 μm, and cell (fluid) velocity of 0.3 μm/s], we found that the net force to move this column of water was on the order of 1 pN. Usami et al, observing confined neutrophils in micropipettes (22), and others in unconfined settings (23)(24)(25), have shown that forces on the order of tens of nanonewtons are required to stall cell motion.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented here are the continuation of the analysis of a modeling framework that has been used to explain a variety of phenomena related to actin dynamics [25], [29], [39], [40]. The derivation of the extension of the model in the form used here has been described in detail in ref.…”
Section: Introductionmentioning
confidence: 92%
“…The exponent w is positive for keratocytes, between 6 and 8, and was determined independently by aspect ratio observations and force measurements (118,152). Contrary to cell measurements, in vitro measurements and theoretical models of actin growth show a rapidly decreasing force-velocity curve, thus proving that actin dynamics alone are insufficient to explain cell measurements, and that either motor activity should be taken into account, or the length change of actin filaments under force (353). Moreover, the ability of the keratocyte cytoskeleton to return to its original shape between successive stalling experiments is striking since no effect of force or velocity change is found after the lamellipodium has been stalled, contrarily to atomic force microscopy in vitro measurements of growing actin networks (118,235).…”
Section: The Mechanics Of the Lamellipodiummentioning
confidence: 99%